2014
DOI: 10.2298/abs1401043r
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A and B viruses in the population of Vojvodina, Serbia

Abstract: At present, two influenza A viruses, H1N1pdm09 and H3N2, along with influenza B virus co-circulate in the human population, causing endemic and seasonal epidemic acute febrile respiratory infections, sometimes with life-threatening complications. Detection of influenza viruses in nasopharyngeal swab samples was done by real-time RT-PCR. There were 60.2% (53/88) positive samples in 2010/11, 63.4% (52/82) in 2011/12, and 49.9% (184/369) in 2012/13. Among the positive patients, influenza A virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The high rate of participants with elevated pre-vaccination titers to the B strain (approximately half of the participants tested) and for the H1N1 strain (approximately one-third of the participants tested) exhibiting seroprotective titers at baseline was in line with a recent publication that provides surveillance data for influenza disease in Serbia from the years 2009 to 2015, showing that A viruses were predominant in the first two seasons (2010/11 and 2011/12), with A/H1N1pdm09 in the 2010/11 season; A/H3N2 in the 2011/12 season and B viruses predominant in the 2012/13 season, where both A/H3N2 and A/H1N1 pdm09 were also present. 16 Our study findings, which also showed that 18% of the participants in the placebo group also seroconverted by day 22, suggest that influenza B infection was ongoing at the time of the study. However, recent data from WHO FLUNET (a global web-based tool for influenza virological surveillance) shows influenza circulating predominately from December 2016 (week 50) to early January (week 4) 2017 with prevalence of A/H3N2 and absence of influenza B activity during the study period, which did not corroborate our observation.…”
Section: Discussionsupporting
confidence: 61%
“…The high rate of participants with elevated pre-vaccination titers to the B strain (approximately half of the participants tested) and for the H1N1 strain (approximately one-third of the participants tested) exhibiting seroprotective titers at baseline was in line with a recent publication that provides surveillance data for influenza disease in Serbia from the years 2009 to 2015, showing that A viruses were predominant in the first two seasons (2010/11 and 2011/12), with A/H1N1pdm09 in the 2010/11 season; A/H3N2 in the 2011/12 season and B viruses predominant in the 2012/13 season, where both A/H3N2 and A/H1N1 pdm09 were also present. 16 Our study findings, which also showed that 18% of the participants in the placebo group also seroconverted by day 22, suggest that influenza B infection was ongoing at the time of the study. However, recent data from WHO FLUNET (a global web-based tool for influenza virological surveillance) shows influenza circulating predominately from December 2016 (week 50) to early January (week 4) 2017 with prevalence of A/H3N2 and absence of influenza B activity during the study period, which did not corroborate our observation.…”
Section: Discussionsupporting
confidence: 61%
“…Among them, influenza B viruses are known to primarily infect the human population and spreads as an acute febrile illness with respiratory symptoms. In addition, the influenza B viruses lead to severe and life-threatening medical complications in human such as bacterial pneumonia, encephalitis, myositis, Reye’s syndrome and sinus infection [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The proportions of IgG-positive patients for influenza B in 2011 were 34.3% (93/271), in 2012 were 69.3% (194/280), and in 2013 were 85.4% (264/309) showing a significant increase over time (p-value <0.0001). The majority of subjects who were seropositive for IBVs were adults with age groups aged 30–64 and >65 years with a seropositivity rate of 48.7% and 60.8%, respectively [ 21 ].…”
Section: Discussionmentioning
confidence: 99%